Quid Tacitus . . . ? The Germania and the Study of Anglo-Saxon England - Toswell, M. J. (Florilegium, 2010)
This paper considers the vexed historiography of Tacitus's Germania and its reception history, first among German and other European historians and then among Anglo-Saxonists. It starts with the putative ninth-century Fulda (or Herzfeld) manuscript and the single Renaissance copy which gives rise to a rich vein of German and English nationalism. References to the Germania as a trustworthy source largely end with the Second World War in texts by classicists and historians, but continue to the present day amongst Old English literary specialists. The paper puckishly suggests that perhaps the Agricola might offer more interesting comparisons to Anglo-Saxon heroic poetry.